Nuclear techniques support to assess erosion and sedimentation processes - Zupanc, Vesna (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
Most studies of erosion and sedimentation evaluation in Slovenia have focused on the use of conventional approaches. This paper highlights potential advantages of nuclear techniques to assess soil redistribution magnitude and presents assessment of the initial 137Cs fallout in undisturbed site, located in Šalamenci, Eastern Slovenia. The 137Cs background activity in the selected forested site was evaluated at 7316 2525 Bq m-2 with a coefficient of variation of 34 % (n = 20). This information will be used in future investigations to assess erosion and sedimentation processes of adjacent agricultural fields with 137Cs method.
Keywords: degradacija; erozija; sedimentacija; Slovenia; Slovenija; zemljišča